(untitled) (Fiep Bulletin - online, 2014)
This study aimed at to characterize the teaching-learning-training process in the masculine infantile category of the Handball in the state of Paraná. For so much, took place a descriptive-exploratory research with 29 players and three trainers of three teams of the masculine gender of the infantile category, adopted to the League of Handball of Paraná. The instruments for collection of data consisted of the systematic and direct observation, with filming employment in the training sessions and subsequent categorize of the activities according to the instrument proposed by Nascimento & Barbosa (2000). The data were analyzed through descriptive statistics, specifically frequency and percentile frequency of the conditions and functions of the activities implemented in the training sessions observed. The principal found results pointed out that the trainers used most of the time of the training sessions with activities with emphasis in the training of the technical elements, in that the functions of the tasks prevailed gone back to the fixation of the technique and global acquisition of the technique, except one of the trainers that used the function of application of the technique more frequently. In relationship the conditions of accomplishment of the tasks, the trainers had preference for the tasks of combination of foundations and individual foundation. In general, it can be affirmed that in the organization and structuring of the sessions of training technician-tactics in the Handball in the infantile category, independent of the competitive level of the teams, the directing methodology prevailed, basically centered in the technical elements of the game. The trainers privileged the execution exercises and correction of the technique, in detriment of the variability exercises and application of the technique.